Republic of Uzbekistan : Technical Assistance Report-Multi-Topic Statistics Diagnostic. (IMF Staff Country Reports; Country Report ;, 2021)
At the request of the authorities, a remote multi-topic statistics diagnostic mission for Uzbekistan took place during March 1-19, 2021.1 In close cooperation with officials of the State Committee of the Republic of Uzbekistan on Statistics (SSC), the Central Bank of Uzbekistan (CBU), and the Ministry of Finance (MOF), the mission (i) assessed the collection, compilation, and dissemination practices for the datasets covered by the mission; (ii) identified key high-level priorities and developed a medium-term action plan for statistical improvement and the associated capacity development (CD) needs; and (iii) developed a roadmap for subscription to the Special Data Dissemination Standard (SDDS). The mission covered the following topics: national accounts (NA) and prices, 2 government finance statistics (GFS) including public debt, external sector statistics (ESS), monetary and financial statistics (MFS), and SDDS subscription.